Military Spending and Economic Growth: A 2025 Update - Shimshon Bichler; Jonathan Nitzan (bnarchives.net, 2025)
The start of the second millennium brought a growing sense that capitalism was becoming more `authoritarian' and `illiberal', with various indicators suggesting that `democracy' is waning around the globe, that the protection of human and civil rights is in retreat and that the number and intensity of military conflicts is on the rise. *** This angst is now greatly amplified by the domestic and foreign policies of the new Trump administration. Having returned to office in early 2025, Trump promptly launched a highly publicized crusade against his country's `deep state', with blasé disregard for its laws and con-stitution; announced his intentions to retreat from his country's traditional postwar role as leader and protector of the Western world; and embarked on seemingly unhinged acts against friends (Canada, Mexico, Denmark, Panama and, primarily, Ukraine) while cozying up to long-term foes (Russia). *** One possible consequence of this growing angst is a global `arms race'.
Keywords: O4; P1; L64; 330; arms race; Donald Trump; growth; militarization